Towards Producing Best Practice in the Malaysian Construction Industry: The Barriers in Implementing the Lean Construction Approach. - Abdullah, Shardy; Abdul Razak, Arman; Bakar, Abu Hassan Abu; Sarrazin, Izran (2009)
Various studies in the construction industry have been conducted to develop the best practice that is only not capable of improving organization profit but also assists in producing a systematic work process which will encourage the optimal use of resources.